2022
DOI: 10.1186/s40168-022-01437-2
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the early life gut microbiome in neonates with critical congenital heart disease: multiomics insights and implications for host metabolic and immunological health

Abstract: Background The early life gut microbiome is crucial in maintaining host metabolic and immune homeostasis. Though neonates with critical congenital heart disease (CCHD) are at substantial risks of malnutrition and immune imbalance, the microbial links to CCHD pathophysiology remain poorly understood. In this study, we aimed to investigate the gut microbiome in neonates with CCHD in association with metabolomic traits. Moreover, we explored the clinical implications of the host-microbe interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…12 We also speculate that, as the underlying cause of cardiac NEC may be different than in preterm infants, some providers might assume that HM is not similarly protective for infants with CHD. Both Huang et al's 64 novel research demonstrating similarities between the gut microbiome of preterm infants and those with critical CHD and our findings of strong associations between HM and reduced NEC would discount this assumption. Furthermore, in animal studies focused on the mechanistic relationship between HM and preterm NEC, a common method of NEC-induction involves subjecting mice to hypoxia, infant formula, and introduction of lipopolysaccharide to induce inflammation 73 a process with clear analogies to the SV CHD clinical course.…”
Section: Potential Mechanismsmentioning
confidence: 49%
See 3 more Smart Citations
“…12 We also speculate that, as the underlying cause of cardiac NEC may be different than in preterm infants, some providers might assume that HM is not similarly protective for infants with CHD. Both Huang et al's 64 novel research demonstrating similarities between the gut microbiome of preterm infants and those with critical CHD and our findings of strong associations between HM and reduced NEC would discount this assumption. Furthermore, in animal studies focused on the mechanistic relationship between HM and preterm NEC, a common method of NEC-induction involves subjecting mice to hypoxia, infant formula, and introduction of lipopolysaccharide to induce inflammation 73 a process with clear analogies to the SV CHD clinical course.…”
Section: Potential Mechanismsmentioning
confidence: 49%
“…Knowledge about the gut microbiome of infants with CHD is only beginning to emerge, [64][65][66][67][68][69] and there has been no investigation into HM composition in the context of CHD. A 2022 study by Huang et al.…”
Section: Potential Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing body of research suggests a strong relationship between gut microbiota and a variety of cardiovascular diseases, such as coronary heart disease, aneurysms, and congenital heart disease. [9][10][11] In a clinical trial, Yuan Huang performed metagenomic sequencing on fecal samples from neonates with CHD compared to healthy controls. The results showed that the CHD group had significant gut microbiota disruption, impaired intestinal barriers, and increased systemic inflammation.…”
Section: Introductionmentioning
confidence: 99%